Knowledge and Practices of Pelvic Floor Muscle Exercises in Pregnancy - Sana Gul, Hafiza Saba Hussain, Fatima, Abeera Ajmal, Misbah Amanat Ali, Sadaf Anjum, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pelvic floor dysfunctions are common among pregnant women. Pelvic floor exercises play an important role in prevention of pelvic floor dysfunctions. Aim: To determine the knowledge and practice of pelvic floor exercises among pregnant women during antenatal period. Methodology: An observational cross-sectional study was conducted at gynecology department of private hospitals of Lahore in which 150 pregnant women were enrolled using convenient sampling, through standardized questionnaire. Data was evaluated by using SPSS version 23. Qualitative variables were presented as percentage. Results: The study showed the high percentage of pelvic floor dysfunctions (41%) were observed among pregnant women. Moreover, the large population of women (67%) were having no knowledge about PFMEs. Among those having knowledge, 91% of women were not performing these exercises. Practical Implication: Present study highlighted the significance of pelvic floor muscle exercises during pregnancy. This study also showed awareness and knowledge of females regarding pelvic exercises. These studies are the need of hour to bring more awareness among females to improve pregnancy results. Conclusion: It was concluded that unfortunately, there was knowledge about importance about PFME’s during pregnancy, but practice is low. Keywords: Pelvic Floor Dysfunction, Pelvic Floor Exercises, knowledge and performance.